Recombinant ferritins for multimodal nanomedicine - Yihao Li; Haoyu Gao; Eugenie Nepovimova; Qinghua Wu; Vojtech Adam; Kamil Kuca (Taylor & Francis Group, 2023)
In all living organisms, ferritins are a group of proteins important for maintaining iron homeostasis. Increasing amount of studies has shown that recombinant ferritins can be widely used in multimodal nanomedicine, especially for anticancer treatment and vaccination. Recombinant particles prepared by fusing viral proteins and ferritin subunits produce a better immune response and higher antibody titres. Moreover, actively-targeted ferritin nanoparticles can recognise receptors and deliver natural or chemical drugs specifically to the tumour tissue. In addition, ferritin-linked or loaded with contrast agents or fluorescent dyes can be used as multimodal particles useful cancer theranostics. In this review, we fully summarised the unitisation of recombinant ferritins in multimodal nanomedicine. The research progress of using recombinant ferritins as nanovaccines, nanozymes, and bioengineered nanocarriers for targeted therapy and bioimaging is emphasised.